2020
DOI: 10.3390/ani10081416
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetic Diversity in the Czech Spotted Dog

Abstract: Loss off genetic diversity negatively affects most of the modern dog breeds. However, no breed created strictly for laboratory purposes has been analyzed so far. In this paper, we sought to explore by pedigree analysis exactly such a breed—the Czech Spotted Dog (CSD). The pedigree contained a total of 2010 individuals registered since the second half of the 20th century. Parameters such as the mean average relatedness, coefficient of inbreeding, effective population size, effective number of founders, ancestor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
(66 reference statements)
1
9
0
Order By: Relevance
“…In contrast, only about 20% of the 581 ancestors of the dogs were inbred, with average inbreeding values of 1.8% for all ancestors and 8.8% for inbred ones. These results were similar to or lower than those for other dog breeds obtained by different authors (1,12,(36)(37)(38)58).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, only about 20% of the 581 ancestors of the dogs were inbred, with average inbreeding values of 1.8% for all ancestors and 8.8% for inbred ones. These results were similar to or lower than those for other dog breeds obtained by different authors (1,12,(36)(37)(38)58).…”
Section: Resultssupporting
confidence: 89%
“…Previously, Jansson and Laikre (31) studied the 26 dog breeds registered in Sweden and found that their health status did not depend on the level of inbreeding. Machová et al (38) found that the Czech Spotted dog breed is now relatively healthy despite the high level of inbreeding in most of the active population. It is, however, a unique dog breed, used primarily as laboratory animals, and it was created assuming that the homozygosity level must be as high as possible because all animals had to be genetically almost identical for laboratory purposes.…”
Section: Tab 5 Distribution Of Genetically Tested Animals By Classes ...mentioning
confidence: 99%
“…Pedigree-based inbreeding coefficients (F) vary widely among different dog breeds [ 12 , 13 , 14 ] ( Table S1 ). Czech Spotted Dogs (F = 0.36), Nova Scotia Duck Tolling Retrievers (F = 0.26), American dog guides (F = 0.15/0.26) and Polish Lowland Sheepdogs (F = 0.18) had particularly high inbreeding coefficients [ 15 , 16 , 17 , 18 ]. Other highly inbred dog breeds included Polish Hunting Dogs and Greyhounds, Lancashire Heeler, Ibizan hounds, Bichon frise, Lundehund and Hungarian Border Collies [ 13 , 16 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Closed populations with such a small number of founding animals normally occur in the wild and some even go through in situ speciation [67]. However, the emergence of such populations is more often captured in new breeds of domesticated animals or laboratory strains, in the creation of which humans are directly involved [68][69][70][71]. The most common problem of such populations is severe inbred depression [72].…”
Section: Discussionmentioning
confidence: 99%